FILSAFAT PENDIDIKAN BAHASA ARAB DALAM PERSPEKTIF ISLAM KLASIK: STUDI INTEGRATIF GAGASAN IBNU MISKAWAIH DAN AL-KINDI - Zuliyah Safitri; Kamal Yusuf (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
The Islamic philosophical thought, especially from Ibn Miskawaih and Al-Kindi, has a great influence on the development of education, including Arabic language education. Both combine ethical and intellectual aspects in education, thus providing a foundation for a holistic education system. This study aims to analyze the contribution of the thoughts of these two figures to the philosophy of Arabic language education and its application in modern education and to explore how the values taught by these twophilosophers can be applied in today's Arabic language curriculum. The method used in this study is the literature study method from the works of these two figures and from journals that discuss the thoughts of these two figures. The results of the studyshow that the integration of ethical values from Ibn Miskawaih and philosophical rationality from Al-Kindi enriches the approach to Arabic language education through a holistic curriculum, which combines moral and intellectual aspects in a balanced way.This integration is expected to form students who are not only proficient in Arabic, but also have ethical character and critical thinking skills that are relevant to the challenges of the modern era. Keywords : Ibn Miskawaih, Al-Kindi, Arabic Language Education, Philosophy of Arabic Language Education.